2011
DOI: 10.1007/s10164-011-0279-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and sexual variation in vigilance behavior of goitered gazelle (Gazella subgutturosa) in western China

Abstract: Animals receive benefits from social behavior. As part of a group, individuals spend less time having to be vigilant. This phenomenon, called the ''group size effect,'' is considered the most dominant factor in an animal's demonstrated level of vigilance. However, in addition to group size, many other social and environmental factors also influence the degree of vigilance, including the season of the year and the sex of the individual. In our study, we examined the vigilant behavior of goitered gazelles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…We therefore argue that the forage quality hypothesis as described by Blanchard et al [54] may not apply in closed environments where attraction and provisioning is practised. However, our findings are similar to observations noted in goitered gazelle (Gazella subgutturosa) by Xia et al [29] where seasonal factors had no considerable effect on the level of vigilance but affected other behavioural states. Our findings are contrary to those of Dunham [55] who argue that during the dry season individuals are supposed to spend more time moving and foraging due to insufficient food supply compared to the wet season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We therefore argue that the forage quality hypothesis as described by Blanchard et al [54] may not apply in closed environments where attraction and provisioning is practised. However, our findings are similar to observations noted in goitered gazelle (Gazella subgutturosa) by Xia et al [29] where seasonal factors had no considerable effect on the level of vigilance but affected other behavioural states. Our findings are contrary to those of Dunham [55] who argue that during the dry season individuals are supposed to spend more time moving and foraging due to insufficient food supply compared to the wet season.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, our findings are similar to observations made elsewhere [27,28]. It is acknowledged that males tend to spend more of their time being vigilant compared to their female counterparts [21,29]. Similar observations have been witnessed in impala (e.g., [27,28]), springbok (Antidorcas marsupialis,e.g., [30]), gazelles (Procapra picticaudata e.g., [31,32]), ring-tailed coati (Nasua nasua,e.g., [33]), among others.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed that adult female with fawn would be more vigilance than adult female without fawn. This case also occurred in cattle (Kluever et al 2008), Przewalski's gazelle (Li et al 2009), African oryx (Ruckstuhl & Neuhaus 2009), and goitered gazelle (Xia et al 2011). Adult female with infant spent more time for vigilance to detect predator earlier and escape danger (Xia et al 2011), to protect themselves and their young (Halofsky & Ripple 2008;Xia et al 2011), and to increase infant survival (Lung & Childress 2006).…”
Section: Hayati J Bioscimentioning
confidence: 89%
“…We predicted that it related to the group size that call group size effect; vigilance declines with increases in group size (Roberts 1996). Group size effect has been reported in Tibetan antelope (Lian et al 2007), Tibetan gazelle (Li & Jiang 2008), asiatic ibex (Xu et al 2010), svalbard reindeer (Reimers et al 2011), and goitered gazelle (Xia et al 2011). Several hypotheses have been proposed to explain the mechanism of group size effect including: collective vigilance (Ebensperger et al 2006;Pays et al 2007), detection and dilution (Fairbanks & Dobson 2007;Li & Jiang 2008;Li et al 2012), and social facilitation (Michelena & Deneubourg 2011).…”
Section: Hayati J Bioscimentioning
confidence: 97%
“…The puberty age for the gazelles ( G. subgutturosa ) which have a seasonally polyestrous cycle is 12–14 months. Although their pregnancy periods are reported to be 5–6 months, this period may vary due to climate conditions and food sources (Frazier & Hunt, 1994; Xia et al., 2011).…”
Section: Introductionmentioning
confidence: 99%